The Dynamics of Code Mixing between Arabic and the Minangkabau Dialect in Students’ Speech - Rismawati, Yanda; Novian, Zailani; Ritonga, Arip Rachman; Ajidin, Salsa Hauna; Dalimunthe, Singgar Mantahari (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to identify the patterns of code mixing used by 11th- and 12th-grade students in the religious studies program at State Islamic Senior High School 1 Koto Baru Padang Panjang, who reside in a dormitory that requires daily Arabic communication, and to analyze the factors that trigger its occurrence. Grounded in Suandi’s theoretical classification of inner, outer, and hybrid code mixing, this research examines how these forms appear in students’ spontaneous speech and what socio-linguistic conditions influence their emergence. This study employs a descriptive, qualitative method that incorporates observation and interview techniques. The data for this study were obtained through direct observation of spontaneous dormitory interactions and semi-structured interviews with ten purposively selected 11th- and 12th-grade students of the religious studies program, all of whom are required to use Arabic in daily communication. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the most dominant pattern is inner code-mixing, followed by outer and hybrid forms. Several factors were identified as triggers, including limited mastery of Arabic vocabulary, influence of the Minangkabau mother tongue, socio-cultural habits, expressive needs, media exposure, and practical communication strategies. These results illustrate the complex dynamics of Arabic–Minangkabau linguistic negotiation among dormitory students and highlight the need for contextual and adaptive approaches to Arabic language development that align with learners’ sociocultural realities.